Integrin Trafficking and Tumor Progression - Sejeong Shin; Laura Wolgamott; Sang-Oh Yoon (International Journal of Cell Biology)
Integrins are major mediators of cancer cell adhesion to extracellular matrix. Through this interaction, integrins play critical roles in cell migration, invasion, metastasis, and resistance to apoptosis during tumor progression. Recent studies highlight the importance of integrin trafficking, endocytosis and recycling, for the functions of integrins in cancer cells. Understanding the molecular mechanisms of integrin trafficking is pivotal for understanding tumor progression and for the development of anticancer drugs.